The role of subject-matter content in teacher preparation: An international perspective for mathematics - Schmidt, William H; Burroughs, Nathan A; Cogan, Leland S; Houang, Richard T (Journal of curriculum studies, 2017)
International comparative studies in education provide a fresh perspective on K-12 education policy by enabling countries to learn from each other's approaches. The recently conducted Teacher Education and Development Study-Mathematics provides a worldwide lens by which to examine the role of subject-matter in the preparation of US teachers of mathematics for primary and lower secondary students. More specifically, a previous study looking at the international top-performing teacher preparation programmes identified a common set of learning experiences (topics/content) related to mathematics. This empirically derived international benchmark is used in this paper to examine the quality of the mathematics preparation of future US teachers in various university and college programmes.